Curcumin Promotes Collagen Type I, Keratinocyte Growth Factor-1, and Epidermal Growth Factor Receptor Expressions in the In Vitro Wound Healing Model of Human Gingival Fibroblasts - Rujirachotiwat, Auspreeya; Suttamanatwong, Supaporn (European Journal of Dentistry, 2020)
Objective Curcumin promotes oral wound healing; however, the underlying mechanism remains unknown. We hypothesized that curcumin may regulate gene expression in human gingival fibroblasts (hGFs). This study investigated the effect of curcumin on the expression of wound healing–related genes, collagen type I (COL1), keratinocyte growth factor (KGF)-1, and epidermal growth factor receptor (EGFR), in the in vitro wound healing model of hGFs, as well as the signaling pathway involved in the regulation of these genes by curcumin.Materials and Methods The hGFs were treated with curcumin in the unwounded condition and in the in vitro wound healing model (scratch assay). Gene expression was determined by quantitative polymerase chain reaction. PD98059 was used to elucidate whether extracellular signal regulated kinase (ERK) signaling is involved in the curcumin-regulated gene expression in hGFs. Cell migration was also analyzed by the scratch assay.Statistical Analysis Data were analyzed by independent t-test or one-way analysis of variance (ANOVA) followed by Tukey’s Honestly Significant Difference ( HSD) test.Results In unwounded hGFs, curcumin significantly increased KGF-1 and EGFR expressions but not COL1 mRNA expression. Interestingly, curcumin significantly upregulated COL1, KGF-1, and EGFR expressions in the in vitro wound healing model. Furthermore, PD98059 significantly decreased the curcumin-induced COL1 and EGFR expressions, but did not significantly affect KGF-1 upregulation by curcumin. However, hGF migration was not affected by curcumin treatment.Conclusion Curcumin induced KGF-1 and EGFR expressions in unwounded hGFs. In the in vitro wound healing model, curcumin upregulated COL1 and EGFR expression via the ERK pathway and increased KGF-1 expression, possibly by an ERK-independent mechanism.
Keywords: curcumin; gingival fibroblasts; collagen; KGF-1; EGFR